Pengasuhan Inklusif Dalam Islam: Studi Kasus Ayah Dan Anak Dalam Drama Korea Perfect Family - Fatihatu Khoir Ar Rosyidah; Siti Mutholingah (Pusat Studi Gender dan Anak (PSGA) Universitas Tarbiyatut Tholabah Lamongan, Jawa Timur Indoensia, 2025)
This study explores the concept of inclusive parenting in Islam through the lens of the father-child relationship in the Korean drama Perfect Family. The academic problem addressed is the lack of intersection between Islamic teachings on family dynamics and contemporary media portrayals, specifically in non-Western contexts. This research is distinct in its application of Islamic perspectives to analyze a popular Korean drama, providing an original approach compared to existing literature focused primarily on Western family models. Using qualitative content analysis, this study examines how inclusive parenting is portrayed, emphasizing mutual respect, empathy, and education within the family. The findings highlight the importance of inclusive parenting in Islamic thought and its representation in modern media. Future research could further explore the comparative analysis of Islamic parenting models in global media, including Western contexts.